2014
DOI: 10.1080/02640414.2014.921830
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of preferred and non-preferred handballing in Australian football

Abstract: In Australian football (AF), handballing proficiently with both the preferred and non-preferred arm is important at elite levels; yet, little information is available for handballing on the non-preferred arm. This study compared preferred and non-preferred arm handballing techniques. Optotrak Certus (100 Hz) collected three-dimensional data for 19 elite AF players performing handballs with the preferred and non-preferred arms. Position data, range of motion (ROM), and linear and angular velocities were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…15 Players need to make fast and accurate perceptual and anticipatory judgments in time-constrained conditions in regard to player and ball movements as the game unfolds. 16 Although both lateral sides can be used for kicking and handling in AF, 17 most elite players exhibit a strong ‘footedness’ preference 18 and coaches expect the dominant foot to be used in most instances. 19 The frequency of left-footed players in AF is estimated to be approximately 20%, based on the number of professional players to have made at least one first-grade appearance during the 2015 season, 20 and so this may provide frequency dependent (dis)advantages.…”
Section: Introductionmentioning
confidence: 99%
“…15 Players need to make fast and accurate perceptual and anticipatory judgments in time-constrained conditions in regard to player and ball movements as the game unfolds. 16 Although both lateral sides can be used for kicking and handling in AF, 17 most elite players exhibit a strong ‘footedness’ preference 18 and coaches expect the dominant foot to be used in most instances. 19 The frequency of left-footed players in AF is estimated to be approximately 20%, based on the number of professional players to have made at least one first-grade appearance during the 2015 season, 20 and so this may provide frequency dependent (dis)advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The ability to perform skills bilaterality is widely believed to be a key characteristic of high-level sports performers because it increases the likelihood of players finding a solution for each scenario they face ( Dillon et al, 2022 ; Moore, O’Dwyer, et al, 2017 ; Parrington & Ball, 2015 ; Stöckel & Vater, 2014 ). There is some support for this position in that Murray et al (2023) found that bilateral Gaelic football players were more likely to be selected for a county under 17 team than their more unilateral counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral skill symmetry is the degree to which an individual can successfully perform with both sides of the body ( Stöckel & Weigelt, 2012 ); it is widely believed to be a key characteristic of high-level sports performers ( Moore, O’Dwyer, et al, 2017 ; Parrington et al, 2015 ). Indeed, Stöckel and Weigelt (2012) suggested that a certain degree of bilateral competence is essential if athletes are to be successful in modern team sports.…”
Section: Introductionmentioning
confidence: 99%
“…However, the compulsory use of the non-preferred side in bilateral practice also lead the body to create new standards of action (Haaland & Hoff, 2003) and to complete a determinant successful action while on the soccer field (Hansen et al, 1999; Reilly et al, 2000b; Vaeyens et al, 2006). The effectiveness of learning to control the ball with the NPL may be related to the similarity of the technical movement patterns in the practice of both sides of the body (Parrington et al, 2015) and/or to the dominant eye, which permits priority treatment of all information in the visual field to result in faster reaction times (Mapp et al, 2003).…”
Section: Discussionmentioning
confidence: 99%